Contemporary Islamic painting in Malaysia: 1980 to 2000 / Ahmad Rashidi Hasan - Hasan, Ahmad Rashidi (2010)
One important aspect that was neglected in the development of Modern Malaysian Art is the development of Islamic art. The decades of 80's and 90'sappeared to be the most active period of the resurgence of Islamic art in Malaysia and this was marked by the numerous Islamic Art exhibitions, seminars and discussions especially in the 90's. Nevertheless, literature on the subject seems scanty which in turn force the researcher to focus on the artwork itself as a visual document of its time. This study is about the Islamic forms, substances, interests and the manifestations of the artworks. 83 samples were collected by using the judgmental sampling methods from a population of 520 artworks by Muslim artists of the 80's and 90's. Observations, by using the Content Analysis methods were carried out to analyze the form and content of these samples. Interviews were also carried out employing art historians and artists as respondents to collect additional and supportive data regarding development of Islamic Art in Malaysia.